Speed Control in Industrial Motors (Ingeniería, Sostenibilidad y Sociedad, 2021)
In industries, whether in automation or assembly lines, the implementation of electric motors is necessary. which is why many companies rely on the work performed by these machines and have implemented motors in almost all industrial settings. Due to the high power produced by these machines, it is very important to develop a computer program that allows me to control the speed of the motors in order to avoid massive power surges that could cause permanent damage to the system comprising these motors and even lead to the shutdown of their service or production.
Keywords: speed; engines; drivers